Effect of a new transpedicular vertebral device for the treatment or prevention of vertebral compression fractures: A finite element study. (February 2023) - Hambli, Ridha; De Leacy, Reade; Vienney, Cécile
Abstract: Background: A finite element study was performed to investigate the biomechanical performance of a novel transpedicular implant (V-STRUT©, Hyprevention, France) made of PEEK (polyetheretherketone) material in terms of strengthening the osteoporotic vertebra and the thoraco-lumbar spine. The objective was to assess numerically the efficacy of the implant to reduce the stress distribution within bone and absorb part of the stress by the implant thanks to its optimized material selection close to that of normal bone. Methods: A numerical model was generated based on a scan of an osteoporotic patient. The model is composed of three consecutive vertebrae and intervertebral discs. A heterogeneous distribution of bone material properties was assigned to the bone. In order to investigate the rationale of the device material selection, three FE models were developed (i) without the device to serve a reference model, (ii) with device made in Titanium material and (iii) with device made in PEEK material. Stiffness and stress distribution within the spine segment were computed and compared in order to assess the implants' performances. Findings: The results obtained by the simulations indicated that the novel transpedicular implant made of PEEK material provided support to the superior vertebral endplate, restored the thoraco-lumbar spine segment stiffness and reduced the stress applied to the vertebrae under the compressive load. Interpretation: Implant geometry in combination with its material properties are very important factors to restore vertebral strength and stiffness and limiting the risk of fracture at the same vertebra or adjacent ones. Highlights: A finite element model was built to assess the performance of a novel transpedicular implant. The model is based on a 3D scan of a patient composed of three vertebrae, discs and ligaments. A heterogeneous bone material properties was assigned to the vertebrae using the grey scale level. Upper vertebra is loaded by applying a compressive loading of 1 MPa on the upper surface of the model. The implant restored the spine stiffness and reduced the stress applied to the vertebrae.